The Quantitative Minor Injury Scale: Pilot Study of a Scale to Measure Level of Minor Injury after Motor Vehicle Collisions - Brickman, Kristopher A.; Blair, Alex B.; Tamburrino, Marijo B.; Dzurik, Alexander D.; Xie, Hong; Smirnoff, Jennifer B.; Wang, Xin (Translation: The University of Toledo Journal of Medical Sciences, 2014)
Study objective: Severity of physical injury after motor vehicle collisions (MVC) may associate with survivors’ mental health; however the quantitative relationship is poorly understood. This is partly because existing injury scales are only sensitive in the potentially fatal range, while most MVC injuries are minor. To quantitatively describe a minor injury, a Quantitative Minor Injury Scale (QMIS) was developed based on injury symptoms, medication, imaging examination, age and hospital stay. Methods: We developed the QMIS after analyzing existing injury and trauma scales coupled with input from Emergency physicians. We recruited 32 MVC survivors with minor injury (rated 1-2 on Abbreviated Injury Scale) who visited the emergency department (ED) within 48 hours of the accident. Depression symptoms were measured by the Center for Epidemiologic Studies Depression Scale (CES-D) within 3 weeks of the trauma and their injuries were quantified with the QMIS. Results: Application of the QMIS in the MVC survivors produced a gradient from 0.6 to 7.8 with an average of 2.65. A significant correlation (R=0.366; p=0.039; n=32) was found with the QMIS score and depression symptoms as measured by the CES-D. Conclusion: Results suggest the QMIS creates differentiation among a population of minor injury patients and may be useful in examining the relationship between minor injury and psychological conditions. The further development of QMIS may generalize the usage of this scale to minor injuries caused by other types of trauma.